Adsorption of Congo Red Dye from Aqueous Solutions by Wheat husk - abeer I alwared; Israa Sabah (Journal of Engineering, 2019)
The Wheat husk is one of the common wastes abundantly available in the Middle East countries especially in Iraq. The present study aimed to evaluate the Wheat husk as low cost material, eco-friendly adsorbents for the removal of the carcinogenic dye (Congo red dye) from wastewater by investigate the effect of, at different conditions such as, pH(3-10), amount of adsorbents (1-2.3gm/L),and particle size (125-1000) μm, initial Congo red dye concentration(10, 25 , 50 and 75mg/l)  by batch experiments. The results showed that the removal percentage of dye increased with increasing adsorbent dosage, and decreasing particle size. The maximum removal and uptake reached (91%) , 21.5mg/g, respectively for 25 initial concentration, pH 6.7 and 1.5 g/l Wheat husk dosage. The experimental data fitted well to Langmuir isotherm mode. The kinetic data support the assumptions of chemisorption were indicates a good fitting to the pseudo-second-order model.